Local communities’ perception towards Banghuris Homestay in Selangor, Malaysia / Muhammad Hanif Othman - Othman, Muhammad Hanif (2023)
The Malaysia homestay programme began informally in the 1970s with the involvement of the local community, who provided accommodation, breakfast and dinner to foreign tourists upon charging at minimal prices compared to hotels and resorts (Hamzah, 2008; Kayat, 2009; Ibrahim & Abdul Razzaq, 2010). At that time, most of the Malays, who lived in Malay ‘kampungs’ (villages) along the coastal and rural areas turned their houses as homestays for tourists (Ibrahim & Abdul Razzaq, 2010). In 1988, with the encouragement and support from the Ministry of Tourism, a commune of five villages in Pahang—consisting of Desa Murni Sanggang, Desa Murni Ketam, Desa Murni Perangap, Desa Murni Sonsang, and Desa Murni Kerdau—established the Desa Murni Homestay as a model for the new Malaysian Homestay Programme (Kayat & Nor, 2006). These villages are located in the Desa Murni area, which is a 15-minute drive from Temerloh, Pahang (Pusiran & Xiao, 2013). This homestay programme in turn, brought cultural, social, environmental, and economic benefits to the local population.